Compound Heterozygous Mutations in TMC1 and MYO15A Are Associated with Autosomal Recessive Nonsyndromic Hearing Loss in Two Chinese Han Families - Pengcheng Xu; Jun Xu; Hu Peng; Tao Yang (Neural Plasticity)
Genetic hearing loss is a common sensory disorder, and its cause is highly heterogeneous. In this study, by targeted next-generation sequencing of 414 known deafness genes, we identified compound heterozygous mutations p.R34X/p.M413T in TMC1 and p.S3417del/p.R1407T in MYO15A in two recessive Chinese Han deaf families. Intrafamilial cosegregation of the mutations with the hearing phenotype was confirmed in both families by the Sanger sequencing. Auditory features of the affected individuals are consistent with that previously reported for recessive mutations in TMC1 and MYO15A. The two novel mutations identified in this study, p.M413T in TMC1 and p.R1407T in MYO15A, are classified as likely pathogenic according to the guidelines of ACMG. Our study expanded the mutation spectrums of TMC1 and MYO15A and illustrated that genotype-phenotype correlation in combination with next-generation sequencing may improve the accuracy for genetic diagnosis of deafness.